Importance of pilot study and data quality control in designing complex training programs for young athletes - Buranarugsa, R.; Oliveira, J.; Maia, J. (The Open Sports Sciences Journal, 2012)
The aims of this pilot study were to use various muscular strength and performance evaluation procedures to assess the preliminary responses from young Thai male athletes to strength training programs, and to apply data quality control to assess data reliability. Sixteen young Thai male athletes aged 13-17 years from the Khon Kaen Sport School were sampled: eight were soccer players and eight were track and field athletes. Subjects were divided into two groups: a complex training group (n = 8) and a resistance training group (n = 8). The pilot intervention program was applied twice a week during two weeks. Maximum strength, anaerobic power, vertical jumps, 40-yard sprints, agility and sports skills were measured before and after the two-week training programs. As expected no significant changes were observed in all measured variables from pre- to post-testing in both groups (p>0.05); mean differences between pre- and post-testing of all variables were close to zero, and high reliability values were observed. All subjects handled well the training programs and assessments. No injuries occurred during all training and testing sessions. The training programs and testing procedures were suitable and safe for young male Thai athletes. Results from statistical analysis showed the achievement of high quality data. Further research in this cohort can be done under a well-designed training program and close supervision by researchers.